Circularly Polarized Photodetectors Based on Chiral Materials: A Review - Zhang, Can; Wang, Xiaohong; Qiu, Longzhen (Frontiers in Chemistry, 2021)
Circularly polarized light (CPL) plays an important role in many photonic techniques, including tomographic scanning based on circular polarization ellipsometry, optical communication and information of spin, and quantum-based optical calculation and information processing. To fully exploit the functions of CPL in these fields, integrated photoelectric sensors capable of detecting CPL are essential. Photodetectors based on chiral materials can directly detect CPL due to their intrinsic optical activity, without the need to be coupled with polarizers and quarter-waveplates as in conventional photodetectors. This review summarizes the recent research progress in CPL photodetectors based on chiral materials. We first briefly introduce the CPL photodetector and its working principles, CPL photodetectors based on different types of chiral materials are introduced. Finally, current challenges and future opportunities in the development of CPL photodetectors are prospected.